The art of deception: Mediated communication strategies in customs and excise fraud - Kristanto, Septian Dawang; Rahmanto, Andre Noevi; Satyawan, Ignatius Agung (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
Current technological developments also play a role in the birth of new crimes in the world, call it cybercrime. This study discusses cybercrime: fraud on behalf of Customs within the scope of persuasion communication and mediated communication from perpetrators to their victims and seen through the theory of Computer Mediated Communication (CMC) and Elaboration Likelihood Model, and also saw the campaign "beware of fraud on behalf of Customs" carried out by the Directorate General of Customs and Excise (DGCE). This research uses a qualitative approach by studying documentation related to fraud on behalf of Customs and interviewing several primary sources involved in handling the case. In addition to looking at the communication strategies implemented by the DGCE, this study will also show the development of communication patterns in the process of deception shown through the phases of impersonal, interpersonal, and hyperpersonal communication. The results of the analysis also showed that persuasion efforts emerged by fraudsters by directing their victims through peripheral routes, resulting in changes in attitude (deceived) and finally give some money to the perpetrator. Furthermore, if the peripheral route is not enough to deceive the victim, the fraudster switches to using the central route to persuade the victim through aspects of motivation, ability, and strong argumentation. This research aims to prevent people from falling victim to fraud. Addressing this issue will require cooperation from all parties, including the government, law enforcement, and the public.